Analysis of Leadership and Recognition of Employee Performance with Work Motivation as a Mediating Variable in the Office Medan Barat District Office - Maswan Harahap; Erwansyah Erwansyah; Hernawaty Hernawaty (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
government agencies, including the West Medan Sub-District Office. Variations in service quality, timeliness of work completion, and employee initiative levels indicate that employee performance is not yet optimal. This study aims to analyze the influence of leadership and rewards on employee performance, both directly and indirectly through work motivation as a mediating variable. This study uses a quantitative approach with a census method of all 60 civil servants at the West Medan Sub-District Office. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with the help of the SmartPLS application. The results show that leadership has a positive and significant effect on employee performance and work motivation. Rewards were also found to have a positive and significant effect on employee performance and work motivation. Furthermore, work motivation had a positive and significant effect on employee performance. Testing for indirect effects showed that work motivation acted as a significant mediating variable in the relationship between leadership and rewards on employee performance. These findings indicate that improving employee performance does not only depend on leadership and reward systems, but is also greatly influenced by the level of employee work motivation. This study is expected to be taken into consideration by the leadership of the West Medan Sub-District Office in formulating policies to strengthen leadership, improve reward systems, and increase work motivation in order to realize more effective and higher-quality public services.